Numerical investigation on the exhaust gas combustion of an SOFC in a catalytic multichannel burner - Yanyi, Yao; Weijuan, Yang; Jingyi, Chen; Xiaoyu, Zhu; Junhu, Zhou (Frontiers in Energy Research, 2024)
The utilization of exhaust gas of solid oxide fuel cell is important to improve the energy efficiency and control pollutants emission. In this work, the combustion of solid oxide fuel cell exhaust gas (H2/CO) in honeycomb ceramic catalytic burner is investigated numerically. A 2D numerical combustion model with 17 channels is built to analyze the influence of channel position on thermal performance and combustion characteristics. The high burnout of H2 and CO is obtained of 96.75% and 97.75% respectively. The channels can be divided into three groups from inner to outside: Part-1, from 9 th channel to 13 th channel; Part-2, from 14 th channel to 16 th channel; Part-3, the 17 th channel.The channels in the same group presented same results of flow, temperature and combustion.Compared with the other channels, the outermost channel shows obvious differences in depressing the temperature of the whole channel, moving the maximum temperature downstream, enlarging the temperature bias of the lower and upper wall and enlarging the combustion zone. H2 and CO perform different combustion process in the honeycomb ceramic catalytic burner. Compared with H2, the initial position of CO conversion is more affected by channel distribution. In 17 th channel, the CO oxidation rate is controlled mostly by the slower oxygen adsorption and the resulting low O(s) coverage. In 9 th channel, the CO oxidation rate is controlled mostly by the wall temperature and fuellimited. The burnout rate of H2 changes from 95% to 99.9% with the channel position, but the burnout of CO varies little. The closer the channel is to the outer, the higher proportion of heterogeneous reaction and more generated heat were observed. The generated heat by the channel can present a diversity of 4%.